THE INFLUENCE OF DISCIPLINE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PT. BANYU TATA UDARA WITH MOTIVATION AS A MEDIATING VARIABLE - Rahmat Nugroho Feri; Cecep Haryoto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The impact of organizational culture and discipline on employee performance at PT. Banyu Tata Udara is investigated in this study using motivation as a mediating variable. Data was collected through questionnaires completed by 160 employees, and Smart PLS's Structural Equation Modeling (SEM) tool was used to quantitatively assess the results. The results of the study show that corporate culture and discipline have a positive and significant impact on motivation, with values of 0.370 and 0.523, respectively. Employee performance is positively impacted by organizational culture and discipline as well, with correlations of 0.228 and 0.269, respectively. With a value of 0.471, employee performance is positively impacted by motivation. Additionally, with values of 0.428 and 0.472, respectively, discipline and organizational culture have an impact on employee performance through motivation.